Determinan Faktor Non-Financial Perusahaan terhadap Financial Performance - Antika, Rindi; Kinasih, Hayu Wikan (AKSES: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to determine the influence of company non-financial factors, namely Environmental Performance and Corporate Social Responsibility, on Financial Performance. The population used in this research is all companies indexed by IDX-IC in 2019-2021. The sample in this research was obtained using a purposive sampling method and obtained a total of 80 observation data. The data used is secondary data and the analysis technique used is multiple linear regression analysis. The research results show that Environmental Performance has an effect on Financial Performance, while Corporate Social Responsibility has no effect on Financial Performance.Keywords: Environmental Performance; Corporate Social Responsibility; Financial Performance.